Positive Effect of Gushukang on Type-H Vessel and Bone Formation - Li, Wantao; Zhou, Xiaoqing; Jiang, Tiejian; He, Hongbo; Wen, Ting (Frontiers in Cell and Developmental Biology, 2020)
Gushukang (GSK) is a herbal compound medicine that has been used for a long time in China for the treatment of osteoporosis. Multiple studies have been conducted to understand the functions of GSK but its specific underlying mechanisms remain unclear. In our study, we cultured osteoblasts and osteoclasts with GSK serum of low dose and high dose and administered 3-month-old mice with 4 g/kg/day and 8 g/kg/day of the GSK solution. GSK was found to promote osteoblast and inhibit osteoclast differentiation in vitro. Mice in the GSK groups had increased bone mass as measured by the Micro-CT. Results of the Tartrate Resistant Acid Phosphatase (TRAP) and the Osteocalcin (OCN) staining suggested decreased bone resorption and increased bone formation in the GSK groups. Furthermore, we discovered a new effect of GSK that induced the formation of the type-H vessels in mice. The mechanism was further explored at the molecular level as we suspected that this function maybe related to an overexpression of the hypoxia inducible factor-1 (HIF-1α). Our study confirmed the function of GSK for prevention of osteoporosis.